Conservative management of De Quervain's tendinopathy with an orthopedic manual physical therapy approach emphasizing first CMC manipulation: a retrospective case series. - Young, Scott W.; Young, Thomas W.; MacDonald, Cameron W. (Physiotherapy Theory & Practice, 2022)
De Quervain's tendinopathy (DQT) is a musculoskeletal disorder that limits hand function of affected individuals. Management of DQT can include splinting, activity modification, medications, corticosteroid injections, physical therapist management, and surgery. There is limited evidence to support the combination of manual therapy and exercise interventions within an Orthopedic Manual Physical Therapy (OMPT) approach when managing patients with DQT. Three patients identified with DQT underwent a multi-modal treatment regimen including carpometacarpal (CMC) thrust and non-thrust manipulation, end range radiocarpal mobilization, mobilization with movement (MWM), strengthening exercises, and grip proprioception training. Outcomes were assessed using the numeric pain rating scale (NPRS), Jamar hand dynamometer grip strength, and the Quick Disabilities of the Arm, Shoulder, and Hand (Quick DASH) questionnaire. These measures were administered at baseline and discharge. Each patient demonstrated improvements in all outcome measures and required ten visits or less to reach a satisfactory outcome. The NPRS improved by a mean of 7.1 points on a 0–10 scale, Quick DASH improved by an average of 37.1%, and grip strength improved by a mean of 27.6 pounds. Each patient was able to return to daily tasks without pain and all improvements were maintained at six month follow-up. An impairment based OMPT management approach was effective in managing three patients with DQT. The inclusion of first CMC manipulation within this multi-modal approach may enhance conservative management of patients with DQT. Because a cause and effect relationship cannot be inferred from a case series, further research is recommended to investigate the efficacy of this management approach.